Pengaruh Mata Kuliah Entrepreneur Dan Literasi Digital Terhadap Kesiapan Berwirausaha Di Era Digital Mahasiswa Program Studi Pendidikan Ekonomi Universitas Bhinneka PGRI Tulungagung - Andik Ferdian Yusuf; Sulastri Rini Rindrayani (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This study aims to determine the effect of entrepreneurship and digital literacy courses on the entrepreneurial readiness of students of the Economic Education study program at the University of Bhinneka PGRI Tulungagung. This research is a correlational quantitative research. The variables studied in this study are entrepreneurship courses (X1), digital literacy (X2) and entrepreneurial readiness (Y). The population in this study amounted to 130 students of the Economic Education study program at the University of Bhinneka PGRI Tulungagung who had received the Entrepreneur 1 and Entrepreneur 2 courses. The sampling technique used in this study was Startified Random Sampling. level 10% of the population of 130, namely 56 students. Data collection techniques using questionnaires or questionnaires. The data analysis technique used is the IBM SPSS Statistics 25 program for windows. The results of the t-test research proved that (Entrepreneur Course X1) obtained the value of t_count (2,931) > t_table (2,005 ) and (Digital Literacy X2) obtained the value of t_count ( 2,800 ) > t_table (2,005 ) it can be partially concluded that "there is an influence entrepreneur and digital literacy towards entrepreneurship readiness”. The F test shows that the value of F_count (141.739) > F_table (3.17). This shows that there is a positive influence on the variables of entrepreneurship courses and digital literacy on the entrepreneurial readiness of students of the economic education study program at the University of Bhinneka PGRI Tulungagung. The value of R2 is 0.842 that affect entrepreneurial readiness. or 84.2%, while there are 15.8% influenced by other factors outside the X1 and X2 variables